The Effect of Syariah Financing Savings and Loan Cooperative to Improving Micro, Small and Medium Enterprises - Nasrullah, Nasrullah (International Conference on Islamic Economic (ICIE), 2022)
National development is a sustainable development effort in the context of realizing a just and prosperous society. To achieve this goal, the government undertakes development in various fields, one of which is economic and financial development. In this economic and financial sector, one of the sectors that plays an important role and has a strategic position in the context of realizing national goals is the banking sector. One of the very rapid economic growths is the Cooperative or Baitul Maal Wat Tamwil (BMT) or the Integrated Independent Business Center is an informal microfinance institution that is operated on the principle of profit sharing, fosters micro and small business businesses, in order to raise the degree and dignity and defend the interests of the poor. The development of BMT in Indonesia began with the establishment of Bank Muamalat Indonesia (BMI) in 1992, which in practice BMI in its operational activities are based on Sharia values. The BMT or Cooperative which is the subject of this research is KSPPS NURI which is located at Jl. Gate 170 Pamekasan. KSPPS NURI has a wide range of products. Namely financing products and savings products. The focus of this research is the influence of KSPPS NURI in increasing micro-enterprises in the village of Blumbungan. Based on the background above, the main problems in this study are: first, how far does the Blumbangan residents know about KSPPS NURI, and second, how is the Effect of KSPPS NURI in developing Micro Enterprises in Blumbungan Village, Kec. District Larangan. East Java, Indonesia. The method used is a quantitative approach. Quantitative methods are basically scientific characteristics to obtain data with certain goals and uses. Based on the result by Cronbach's Alpha Reliability Level, it can be concluded that the Correlation Interval value is greater than 0.600 (medium interval value). This shows that the questionnaire is stated to be very strong based on the total value of the interval on the questionnaire 0.853 0.600. based on the Validity Test, it is known that item 1 gets a score of 0.704, item 3 gets 0.694 using a significance test of 0.05 or an r-table significance value of 0.632, meaning that item 1 and item 3 are declared valid because the r-count value is greater than the r-table. Furthermore, on item P2 a score of 0.766 was obtained, P4 a score of 0.898 and P5 a score of 0.905 using the r-table significance test of 0.765, meaning that items P2, P4 and P5 were declared valid because the r-count value was greater than r-table. Based on the results of interviews and questionnaires found by the researchers, it can be concluded that the presence of KSPPS NURI has an influence in increasing the Micro Enterprises of its Members or Customers who are domiciled in the village of Blumbungan.